Analisis Efektivitas Sistem Informasi Akuntansi terhadap Prosedur Bongkar Muat pada PT Pelabuhan Indonesia (Persero) Regional 4 Bitung - Fardiana, Fadillah Mutiara Nahza; Pusung, Rudy J.; Lintong, Diana Nova (Yayasan Widyantara Nawasena Raharja, 2025)
Loading and unloading activities at PT Pelabuhan Indonesia (Persero) Regional 4 Bitung play an important role in supporting the smooth flow of logistics and operational efficiency of the company. However, loading and unloading processes that are not fully integrated in real time have the potential to cause delays in information, cost inefficiencies, and obstacles in internal control. This study aims to analyze the effectiveness of the implementation of the Accounting Information System (AIS) on loading and unloading procedures in improving the efficiency and accuracy of the company's operational data management. This study uses a qualitative case study method with data collection techniques through interviews and documentation at the Finance Division of PT Pelabuhan Indonesia (Persero) Regional 4 Bitung. The results show that the company has implemented a system capable of recording, controlling, and reporting loading and unloading activities in an integrated and real-time manner. Based on an analysis using the five components of COSO internal control, the accounting information system implemented is considered to be effective. This system produces accurate information, improves time and cost efficiency, strengthens internal control, and supports the application of the Just In Time (JIT) principle in operational activities.